2005
DOI: 10.1016/j.jacc.2004.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic and electrophysiologic characteristics of ventricular tachycardia originating within the pulmonary artery

Abstract: Ventricular tachycardia originating within the PA has different electrocardiographic and electrophysiologic characteristics from that originating from the RV-end-OT. When mapping the RVOT area, the catheter may be located within the PA if a low-voltage atrial or local ventricular potential of <1-mV amplitude is recorded. Heightened attention must be paid if RFCA is required within the PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
4
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 18 publications
2
124
4
3
Order By: Relevance
“…[4] On the other hand, no significant differences were detected in other parameters including aVL/aVR ratio of Q-wave amplitude and R/S ratio on lead V2 (Table 3), probably because of a small number of patients in our study. A recent study reported that an initial PVC with positive QRS complex in lead I was observed in about 70 % (10 out of 14) of patients with idiopathic polymorphic VT / VF arising from RVOT.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…[4] On the other hand, no significant differences were detected in other parameters including aVL/aVR ratio of Q-wave amplitude and R/S ratio on lead V2 (Table 3), probably because of a small number of patients in our study. A recent study reported that an initial PVC with positive QRS complex in lead I was observed in about 70 % (10 out of 14) of patients with idiopathic polymorphic VT / VF arising from RVOT.…”
Section: Discussioncontrasting
confidence: 61%
“…However, there were no significant differences in the ECG characteristics such as QRS duration, R/S ratio and R-wave duration index in lead V2, aVL/aVR of Q-wave amplitude, and the incidence of positive QRS wave in lead I [4,13,14] (Table 3). 2B).…”
Section: Patient Characteristicsmentioning
confidence: 94%
See 2 more Smart Citations
“…14 It should be noted that ventricular myocardial extensions never occur in the aorta. 10 IVAs can originate from the AV annuli including the mitral annulus 7,8 and tricuspid annulus.…”
mentioning
confidence: 99%